Risk Factors for Gastritis Among Nursing Students: A Cross Sectional Study - Ruhyanudin, Faqih; Rahayu, Dinda Dewi Setyaning; Aribah, Nabilah Hananningtyas; Mukminin, Sania Triadmara Sukma; Alhusna, Chairul Huda; Rohmah, Anis Ika Nur; Ubaidillah, Zaqqi; Wahyuningsi, Indri; Sunardi, Sunardi (Universitas Muhammadiyah Surakarta, 2026)
Gastritis is characterized by symptoms such as nausea, vomiting, dull epigastric pain, upper abdominal discomfort, early satiety, and loss of appetite. Some patients also report dizziness and neck discomfort. Without proper treatment, gastritis may progress to gastroesophageal reflux disease (GERD), causing severe symptoms such as chest pain, heartburn, and sleep disturbances, which can significantly reduce productivity. Gastritis commonly affects individuals in their productive years, including students, due to irregular eating patterns, poor sleep quality, and high stress levels. This study aims to identify the dominant risk factors contributing to gastritis among nursing students. The research of an observational analytic design with a cross-sectional approach was employed. A total of 107 students were purposive sampling technique based on inclusion criteria: being active nursing students with a history of gastritis. Data were collected using dietary patterns questionnaires, Pittsburgh Sleep Quality Index (PSQI), the Depression, Anxiety, and Stress Scales (DASS), and gastritis symptoms questionnaires. Data were analyzed using chi-square and logistic regression with a significance level of p<0.05. Results indicated that 52.3% had poor dietary patterns, 90.7% had poor sleep quality, and 26.2% experienced stress. Logistic regression analysis revealed that stress was the most dominant risk factor (OR=11.78; 95% CI: 3.72–37.29; p<0.001), followed by dietary pattern (OR=2.49; 95% CI: 1.02–6.08; p=0.046), while sleep quality showed no significant association (p=0.448). In conclusion, stress is the primary risk factor for gastritis among nursing students. Therefore, stress management and lifestyle interventions are necessary to prevent gastritis and promote students' well-being.